Bundesstaatliche Identitäten und ihre Achtung im Unionsrecht - Weber, Teresa (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
The book adresses the question how the concept of national identity in EU law relates to federalism and how potential conflicts between EU law and a Member States' federal organisation are resolved. Building on a thorough analysis of Art. 4 para. 2 TEU, three legal systems (Austria, Belgium, Germany) are examined on the basis of a uniform analytical grid in order to identify their respective federal national identities. These are then contrasted with Union law in order to identify potential conflicts, in areas such as fundamental rights and freedoms and state aid law.